Identification and Characterisation of Phenolics in Polygonum capitatum by Ultrahigh‐Performance Liquid Chromatography with Photodiode Array Detection and Tandem Mass Spectrometry. Issue 6 (23rd May 2013) - Liao, Shang‐Gao; Zhang, Li‐Juan; Sun, Fa; Wang, Zhen; He, Xun; Wang, Ai‐Min; Li, Yong‐Jun; Huang, Yong; Lan, Yan‐Yu; Zhang, Bo‐Li; Wang, Yong‐Lin
ABSTRACT: Introduction: Polygonum capitatum is a well‐known Chinese medicinal plant widely used by the Miao people for the treatment of various urologic disorders. Previous investigations have shown the presence of various types of phenolics. Our ultrahigh‐performance liquid chromatography with photodiode array detection and mass spectrometry (UPLC–PDA–MS) analysis indicated that flavonoid glycosides and polyphenolic glycosides were its major constituents and quite a number of phenolic compounds have not yet been identified. Identification or characterisation of the major compounds of this plant will contribute to the scientific understanding of the medicinal plant and the authentication of the plant material and its pharmaceutical preparations. Objective: To develop an efficient method for the identification and structural characterisation of the major compounds present in P. capitatum . Methods: Elution of the 70% ethanol extract of P. capitatum by 80% ethanol on a D101 macroporous resin column afforded a phenolics‐enriched fraction, separation of which by Sephadex LH‐20 column chromatography eluted with absolute ethanol gave a tannin‐free phenolic fraction (TFPF). Compounds present in TFPF were identified and structurally characterised by UPLC–PDA–ESI–MS/MS. Results: An amino acid and 40 phenolics including a number of flavonoid glycosides and polyphenolic glycosides were identified or structurally characterised in TFPF. Among these compounds, four were new and 19 were described in the plant for the first time. Conclusion: The study showed that TFPF of P. capitatum contained flavonoid glycosides and polyphenolic glycosides as its major principles. Polyphenolic glycosides were perhaps the most typical chemical markers of P. capitatum . Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Polygonum capitatum is a well‐known Chinese medicinal plant widely used by the Miao people for the treatment of various urologic disorders. The use of UPLC–PDA–MS/MS has led to the identification or structural characterization of an amino acid and 40 phenolics including a number of known and unknown flavonoid glycosides and polyphenolic glycosides in a tannin‐free phenolic fraction. Results showed that polyphenolic glycosides were perhaps the most typical chemical markers of P. capitatum .